The Dynamics of Multidimensional Poverty in Contemporary Australia - Perales, F; Martinez, A (My University, 2017)
Progressively more researchers argue that successfully measuring social inequalities requires moving from income-based to multidimensional poverty indicators, but evidence on Australia is still largely reliant on the former. Using long-running panel data from the Household, Income and Labour Dynamics in Australia Survey we examine trends in multidimensional poverty in Australia between 2001 and 2013. We find that this has been relatively stable, with some evidence of an upwards trend following from the 2008 Global Financial Crisis. However, a closer examination of the individual components reveals a more dynamic picture. Deprivation concerning health, material resources, social support and education increased over the 13-year observation period, offsetting decreases in deprivation concerning safety perceptions, employment and community participation. Additionally, using counterfactual simulations, we examine the relative roles of different poverty domains in explaining changes in Australian multidimensional poverty. We find that recent year-on-year changes in multidimensional poverty are mainly driven by fluctuations in social support, health and material resources. Altogether, our findings suggest that Australian poverty-reduction policies would enhance their effectiveness and efficiency by focusing on improving disadvantage in the domains of health and material resources.
Keywords: Finance -- Poverty and disadvantage; Income, wealth and finances; Finance; Poverty and disadvantage; Income, wealth and finance